Practical Analysis of Information-based Teaching Methods in E-commerce Courses - Xu, Haoyuan (Journal of Educational Research and Policies, 2025)
With the continuous transformation and development of information technology in the current world, e-commerce is also undergoing continuous optimization and transformation, the teaching methods of e-commerce professional courses also need to be continuously optimized with the development and changes. This article explores the practicality of information technology teaching methods in e-commerce courses, and discusses the problems in evaluation and standards during the teaching process. By analyzing the specific application, implementation effects, and evaluation methods of information technology teaching methods, it attempts to establish a scientific and dynamic practical evaluation system suitable for the school’s main majors, in order to better serve the practical effects of information technology teaching in e-commerce courses at this school. By combining student feedback indicators and teacher evaluation data during the teaching process, we hope to accurately reflect the feedback and effectiveness of our school’s information technology teaching, and provide certain reference basis and ideas for the reform of e-commerce professional teaching.